Presentase Kejadian Nyeri Punggung Mahasiswa Berdasarkan Pemilihan Posisi Duduk Perkuliahan Biostatistik - Mujahidin, Mujahidin (JOURNAL OF HEALTH SCIENCE, 2025)
Background: Choosing a sitting position when following the lecture process is a routine thing and is usually done every day by students, this aims to further maximize the learning process. By occupying a strategic sitting position, it will be easier to interact, either with lecturers or with classmates. However, the selection of this sitting position often causes complaints in the form of back pain if the sitting position occupied is not ergonomic. Methods: This research is a descriptive survey research. The sample in this study was the third semester students of class A1, A2 and A3 totaling 110 students who were selected using purposive sampling technique. This research was conducted in September 2016-February 2017. The results showed that in class A1 there were 6 students (17.0%) with mild pain and 1 person (2.9%) with moderate pain. In class A2 there are 2 students (5.7%) with mild pain and 2 students (5.7%) with moderate pain. In class A3 there are 2 students (5.7%) with mild pain, 1 student (2.9%) with moderate pain and 1 student (2.9%) with severe pain. Conclusion: Of the 110 students who took the biostatistics course, there were 15 students who experienced back pain. Suggestion: choose a strategic and ergonomic position so that back pain during the learning process is not expected to occur. Keywords: Back Pain Percentage, Sitting Position